Bioremediation of cadmium- and zinc-contaminated soil using Rhodobacter sphaeroides. (April 2018) - Peng, Weihua; Li, Xiaomin; Song, Jingxiang; Jiang, Wei; Liu, Yingying; Fan, Wenhong
Abstract: Bioremediation using microorganisms is a promising technique to remediate soil contaminated with heavy metals. In this study, Rhodobacter sphaeroides was used to bioremediate soils contaminated with cadmium (Cd) and zinc (Zn). The study found that the treatment reduced the overall bioavailable fractions (e.g., exchangeable and carbonate bound phases) of Cd and Zn. More stable fractions (e.g., Fe-Mn oxide, organic bound, and residual phases (only for Zn)) increased after bioremediation. A wheat seedling experiment revealed that the phytoavailability of Cd was reduced after bioremediation using R. sphaeroides . After bioremediation, the exchangeable phases of Cd and Zn in soil were reduced by as much as 30.7% and 100.0%, respectively; the Cd levels in wheat leaf and root were reduced by as much as 62.3% and 47.2%, respectively. However, when the soils were contaminated with very high levels of Cd and Zn (Cd 54.97–65.33 mg kg −1 ; Zn 813.4–964.8 mg kg −1 ), bioremediation effects were not clear. The study also found that R. sphaeroides bioremediation in soil can enhance the Zn/Cd ratio in the harvested wheat leaf and root overall. This indicates potentially favorable application in agronomic practice and biofortification. Although remediation efficiency in highly contaminated soil was not significant, R. sphaeroides may be potentially and practically applied to the bioremediation of soils co-contaminated by Cd and Zn. Highlights: Rhodobacter sphaeroides had a remediation effect on soil contaminated with metals. Available metal fractions were transformed to less accessible and inert fractions. Cd phytoavailability was significantly reduced in treated soils. Rhodobacter sphaeroides bioremediation enhanced Zn/Cd ratio in wheat.